Enhanced Raman scattering of graphene by silver nanoparticles with different densities and locations. (14th February 2017) - Sun, Hai-Bin; Fu, Can; Xia, Yan-Jie; Zhang, Chong-Wu; Du, Jiang-Hui; Yang, Wen-Chao; Guo, Peng-Fei; Xu, Jun-Qi; Wang, Chun-Lei; Jia, Yong-Lei; Liu, Jiang-Feng
Abstract: Graphene–metal nanoparticle heterojunctions greatly improve the surface-enhanced Raman scattering (SERS) by strong light–graphene interactions. In this work, to enhance the Raman scattering, Ag nanoparticles (NPs) underneath and on top of the graphene were used. Then, Raman scattering of graphene is significantly enhanced approximately 67-fold, and the enhancement factor of the graphene G peak increases with the Ag NP density at the same location. In addition, an obvious red-shift and broadening of the resonance peak of Ag NPs is presented, which may be correlated to the strength of Raman enhancement, the coupling of the deposited Ag NPs and the graphene. Further, graphene–Ag NP heterojunctions can be used as SERS substrates to obtain the strongest Raman signals of the rhodamine (R6G) molecules and the weakest photoluminescence (PL) background from the Ag NPs. Based on the tunable Raman enhancement, graphene–Ag NPs offer a promising platform for engineering SERS substrates to obtain highly sensitive detection of trace levels of analyte molecules.